Merger & acquisition in Malaysia: Profitability drivers of short-term wealth and post acquisition operating performance / Nurhazrina Mat Rahim and Associate Professor Dr. Pok Wee Ching - Mat Rahim, Nurhazrina; Pok, Wee Ching (Research Management Institute (RMI), 2012)
There is high number of announced M&A deals in Malaysia, little is known about the determinants of short-term wealth effects of M&As in emerging market Malaysia, in particular the third M&A wave. The purpose of this paper is to analyze the short-term wealth effects of M&As in Malaysia. In addition, this study also examines the factors that affect the short-term shareholders' wealth during M&A announcements in Malaysia. The short-term wealth effect is measured by the Cumulative Average Abnormal Returns (CAARs). For the purpose of this study, the wealth effects of a sample of 180 target and 196 bidding companies announced in Malaysia during the period from 2001 to 2009 are analyzed. Results of the study revealed that there are positive market reactions by both target and bidding shareholders towards M&A announcements. However, target shareholders earned significantly higher CAARs than bidding shareholders. There is sufficient evidence to suggest that economic condition surrounding merger announcements, type of acquisition (diversified/related), premium paid and status of bid (successful/failed) affect the short-term wealth effects of target and bidding shareholders during M&A announcements. However, the impact on the target and bidding shareholders are different. Relative size negatively affects bidding shareholders wealth. Target with higher ROE also earned significantly higher returns. In addition this paper also examines the operating performance of the same sample of Malaysian companies involved in Mergers & Acquisitions (M&A). However, the samples used in this analysis are only for the period 2004 to 2008. The analysis is based on accounting measures to test the effects of M&As on the corporate performance of companies. It tests two hypotheses: first, whether there have been significant differences in corporate performance following the M&A event. Second, whether the type of acquisition (related or diversified) has an impact on corporate performance. Empirical results revealed that post-acquisition profitability and asset turnover, on average, show no improvement compared with pre-merger values. Similar result is also obtained for D/E ratio where there is no improvement following M&As. However, companies which acquired target in different industries show significant improvement in asset turnover. Thus, operating synergy was created for companies involved in diversified M&As.